Designing and Developing Smart Plant Information System - Thinagaran, P.; Roslan, M.N.S.; Munuganan, P.; Kasmin, F.; Ahmad, S.S.S.; Othman, Z. (International Journal of Human and Technology Interaction (IJHaTI), 2021)
Pandemic COVID-19 have impacted the way of life of all people in the world. The effect continues worsened when our government-imposed lockdowns and every people need to stay home. Due to too long of staying at home, boredom become  one of the most reported negative psychological effects of the quarantine. It is undeniable that people of all ages enjoy gardening and planting. Hence, this pandemic time can be a golden opportunity for people to get outside of their compound and grow their interest in gardening. Thus, this project is designed to introduce the basic knowledge of plantations in easier and effective way. The system is applicable for multiple users who tend to learn more about plants and its plantation methods. Both men and women can start their own garden with proper planting methods. This system has been developed using several modules such as the leaf recognition using convolutional neural network (CNN), plant disease advice using knowledge based expert system and plant information using chatbot. The leaf recognition using CNN module will help the user to recognize a plant by providing the plant’s leaf image. The plant disease advice will diagnose the certain disease a plant might have by calculating the confidence level of provided symptoms of the disease. Finally, the plant information using chatbot module will provide information about plants by answering the user’s questions. It is hoped that this system could serve as the best smart plant information system to the users